DAMPAK PENGEMBANGAN BIMBINGAN PRIBADI BAGI ANGGOTA UNIT KEGIATAN KHUSUS KORPS SUKARELA PALANG MERAH INDONESIA UNIVERSITAS ISLAM NEGERI SULTHAN THAHA SAIFUDDIN JAMBI - Rahayu , iin (Socious Journal, 2024)
This research is motivated by several problems, namely: the level of independence of members decreases, the reduced attitude of self-discipline in members, leadership attitude has not been embedded, members are less enthusiastic to participate in routine activities and exercises. The type of research used is field research using a qualitative descriptive approach. By emphasizing field data sources as primary data and literature as secondary data. In taking the subject of research the researcher used the Purposive Sampling method. Data collection techniques using observation, interviews and documentation, with data reduction data analysis techniques, data presentation and verification. The researcher stated in this study that the process of developing personal guidance applied in the Special Activity Unit of the Indonesian Red Cross Voluntary Corps of UIN STS Jambi was very good in developing a potential that exists in each of their personalities. Supporting factors in the development of personal guidance for members of the Indonesian Red Cross Volunteer Corps Special Activity Unit of the Sulthan Thaha Saifuddin Jambi State Islamic University have been very good. The inhibiting factors faced by Members of the Indonesian Red Cross Volunteer Corps Special Activity Unit Unit Sulthan Thaha Saifuddin Jambi State Islamic University are few and can still be handled well by the members themselves. The impact of developing personal guidance for members of the Red Cross Voluntary Corps Special Activity Unit Indonesia Sulthan Thaha Saifuddin Jambi State Islamic University, namely positive and negative impacts.